2018
DOI: 10.1371/journal.pone.0208057
|View full text |Cite|
|
Sign up to set email alerts
|

Use of RFID technology to characterize feeder visitations and contact network of hummingbirds in urban habitats

Abstract: Despite the popular use of hummingbird feeders, there are limited studies evaluating the effects of congregation, sharing food resources and increased contact when hummingbirds visit feeders in urban landscapes. To evaluate behavioral interactions occurring at feeders, we tagged 230 individuals of two species, Anna’s and Allen’s Hummingbirds, with passive integrated transponder tags and recorded their visits with RFID transceivers at feeders. For detecting the presence of tagged birds, we developed an RFID equ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 40 publications
(48 reference statements)
1
16
0
Order By: Relevance
“…When at feeders, hummingbirds interact with an average of seven other birds. Male to male interactions tend to happen most frequently followed by male to female interactions and female to female interactions [27]. Our data indicate male Anna's hummingbirds have higher anti-microbial activity than females.…”
Section: Plos Onementioning
confidence: 66%
“…When at feeders, hummingbirds interact with an average of seven other birds. Male to male interactions tend to happen most frequently followed by male to female interactions and female to female interactions [27]. Our data indicate male Anna's hummingbirds have higher anti-microbial activity than females.…”
Section: Plos Onementioning
confidence: 66%
“…We highlight the value of pairing an underutilized passive mark-recapture approach with social network models in the study of foraging patterns of small-bodied organisms (see also [13,18]). We aimed to gain insight into the functional connectivity of high-elevation meadows in the Cascade Mountains in the face of forest encroachment by investigating foraging behaviours of a common pollinator, rufous hummingbirds, in the current landscape.…”
Section: Discussionmentioning
confidence: 99%
“…These methods offer multiple benefits. First, our methods employ passive mark-recapture techniques which may yield large volumes of data with reduced labour cost [13]. Second, sender-receiver models allow us to estimate the effects of landscape features on the connectivity of fixed locations in a generalized regression framework and allow insight into movement patterns such as the reciprocity of movements which may elucidate sourcesink dynamics (emigration out of high-density areas with minimal immigration) and directional gene flow.…”
Section: Introductionmentioning
confidence: 99%
“…Commonly found in urban settings due to the use of man-made feeders, hummingbirds are key pollinator species in urbanized areas ( Maruyama et al, 2019 ). Hummingbird distribution ( Greig, Wood & Bonter, 2017 ), population composition, and intra- and inter species interactions ( Bandivadekar et al, 2018 ; Carpenter, 1987 ; Ditchkoff, Saalfeld & Gibson, 2006 ; Lowry, Lill & Wong, 2013 ; Ng et al, 2004 ; Thomas, Baker & Fellowes, 2014 ) all have been significantly affected due to increased artificial food-resource provisioning, and urbanization. Empirical studies describing disease and health risks in hummingbirds found in urban habitats are still needed.…”
Section: Introductionmentioning
confidence: 99%